2023
DOI: 10.3390/rs15082093
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Cooling Island Effect in Blue-Green Space Based on Multi-Scale Coupling Model

Abstract: The mitigation of the urban heat island effect is increasingly imperative in light of climate change. Blue–green space, integrating water bodies and green spaces, has been demonstrated to be an effective strategy for reducing the urban heat island effect and enhancing the urban environment. However, there is a lack of coupled analysis on the cooling island effect of blue–green space at the meso-micro scale, with previous studies predominantly focusing on the heat island effect. This study coupled the single ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Although the aggregation density of CSB and LST as a whole shows a positive relationship, but in the local area there is a noncorrelation of special cases, the reason may be related to a certain range of building layout or vegetation coverage (Mohajerani et al, 2017;Yao et al, 2018). The results of the article show that the contribution index of the samples in the vegetation coverage area is negative, and we know that water bodies and vegetation usually can mitigate the urban heat island when they are used as blue-green space in cities (Pan et al, 2023;Zhou et al, 2023). Suburban CSB are less affected by blue-green covered areas.…”
Section: Discussionmentioning
confidence: 82%
“…Although the aggregation density of CSB and LST as a whole shows a positive relationship, but in the local area there is a noncorrelation of special cases, the reason may be related to a certain range of building layout or vegetation coverage (Mohajerani et al, 2017;Yao et al, 2018). The results of the article show that the contribution index of the samples in the vegetation coverage area is negative, and we know that water bodies and vegetation usually can mitigate the urban heat island when they are used as blue-green space in cities (Pan et al, 2023;Zhou et al, 2023). Suburban CSB are less affected by blue-green covered areas.…”
Section: Discussionmentioning
confidence: 82%
“…The WRF/UCM model, being a single-layer model, has the capability to replicate the urban blue-green space, encompassing a wide range of urban structures and geometries. This leads to enhanced horizontal weather prediction accuracy and improved boundary conditions for simulations [43][44][45][46][47][48][49][50]. Over the last twenty years, the ESLZ has undergone rapid and uncontrolled urbanization, resulting in the conversion of numerous vacant land parcels into developed, built-up areas.…”
Section: Climate Model Datasetmentioning
confidence: 99%
“…Exposure to GBSs means a closeness with nature, which has several benefits for visitors, including but not limited to better social interaction [41], solid social cohesion [42], improvements in psychological state [18,21,41], and improved physical health [43]. These benefits result from ecosystem services provided by GBSs through mitigating air pollution [44][45][46], cooling the surrounding temperature [47], and adjusting the regional climate [19]. Studies using facial expression scores have fully identified these positive effects with more details about the involvement of driving forces, such as landscape metrics [17,18,20,21], plant diversity [24], regional climate [19,48,49], and air quality [44][45][46].…”
Section: Introductionmentioning
confidence: 99%